Perceptions of the European Space Sector: Youth Engagement With Space Education Events - Roche, Joseph; Bell, Laura; Hurley, Mairéad; Jensen, Aaron M.; Jensen, Eric A.; Owens, Brendan; D’Arcy, Grace; González, Jorge Rivero; Russo, Pedro (Frontiers in Education, 2021)
Space education not only plays a key role in helping young people understand the natural world and their impact on the planet but is also vital in ensuring that future generations can make meaningful contributions to the space sector at all levels. Positive perceptions of the space sector can lead young people to take roles where they can contribute to new knowledge, develop new technologies, and tackle societal challenges. As the relationship between science and society is tested by global events — such as climate change and the COVID-19 pandemic — scientific trust and accountability have become topics of frequent and public debate. The way in which young people engage with space education and perceive their potential involvement with the space sector is of greater importance now than ever before. This paper describes a two-year European space education project that was carried out before and during the COVID-19 global pandemic. An evaluation of the project activities showed that young people are generally enthusiastic about space, but their perceptions of the European space sector — and their connections to it — are less positive. Recommendations are made on the challenges facing the space sector and how it needs to adapt to better support the development of a more inclusive space education community.